2021
DOI: 10.1186/s13000-021-01177-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-stroma ratio as a new prognosticator for pseudomyxoma peritonei: a comprehensive clinicopathological and immunohistochemical study

Abstract: Background As a rare clinical tumor syndrome with an indolent clinical course and lack of pathognomonic symptoms, pseudomyxoma peritonei (PMP) is usually diagnosed at an advanced stage. In-depth pathological analysis is essential to assess tumor biological behaviors, assist treatment decision, and predict the clinical prognosis of PMP. The tumor-stroma ratio (TSR) is a promising prognostic parameter based on the tumor and stroma. This study explored the relationship between TSR and the patholog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In‐depth study of TNs and TCs can reveal more useful information about tumor development. Our previous study showed that the ratio of tumor/stroma area had a significant impact on the prognosis, suggesting the clinical value of TNs area 35 . Choudry et al 19 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In‐depth study of TNs and TCs can reveal more useful information about tumor development. Our previous study showed that the ratio of tumor/stroma area had a significant impact on the prognosis, suggesting the clinical value of TNs area 35 . Choudry et al 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study showed that the ratio of tumor/stroma area had a significant impact on the prognosis, suggesting the clinical value of TNs area. 35 Choudry et al. 19 and Horvath et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation